2021
DOI: 10.1007/s11255-021-03091-3
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome in hemodialysis patients treated with calcium acetate or treated with sucroferric oxyhydroxide: a pilot study

Abstract: Purpose It has been proved that the gut microbiome is altered in patients with chronic kidney disease. This contributes to chronic inflammation and increases cardiovascular risk and mortality, especially in those undergoing hemodialysis. Phosphate binders may potentially induce changes in their microbiome. This trial aimed to compare the changes in the gut microbiome of hemodialysis patients treated with calcium acetate to those treated with sucroferric oxyhydroxide. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(59 reference statements)
0
6
1
Order By: Relevance
“…All in all, it is plausible that out-competition of siderophore-non-producers is reduced under iron plethora conditions. Comparable to our study, overall, both Iguchi et al 6 and Merino-Ribas et al 7 found no significant changes in the gut microbiome after SFOH intake. However, Iguchi et al found a significant increase in the families Clostridiaceae (0.6%, 2.6%, p = 0.0264) and Oscillospiraceae (0.21%, 0.40%, p = 0.023) and the genus Oscillibacter (t0 0.20%, t12weeks 0.44%, p = 0.022).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…All in all, it is plausible that out-competition of siderophore-non-producers is reduced under iron plethora conditions. Comparable to our study, overall, both Iguchi et al 6 and Merino-Ribas et al 7 found no significant changes in the gut microbiome after SFOH intake. However, Iguchi et al found a significant increase in the families Clostridiaceae (0.6%, 2.6%, p = 0.0264) and Oscillospiraceae (0.21%, 0.40%, p = 0.023) and the genus Oscillibacter (t0 0.20%, t12weeks 0.44%, p = 0.022).…”
Section: Discussioncontrasting
confidence: 62%
“…Recently, Iguchi et al 6 found no significant change in bacterial diversity investigating all taxonomic levels, but potential uremic toxins such as serum indoxyl sulfate and p -cresyl sulfate were significantly elevated in the test group. Merino-Ribas et al 7 confirmed the long-term stability of the gut microbiome on SFOH in a pilot study based on seven patients and another five patients switching to calcium acetate as phosphate binder. Both studies were limited to the intestinal microbiome, whereas major effects would be expected to occur in the oral cavity given the rapid disintegration of SFOH in saliva.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Spearman's correlation analysis exhibited that relative abundance of Coprococcus_3 was positively correlated with the levels of trimethylamine N-oxide, indoxyl sulfate, cholic acid, deoxycholic acid and betaine, in serum [84]. Merino-Ribas and his colleague [85] demonstrated that a 5-month treatment with either calcium acetate or sucroferric oxyhydroxide did not affect baseline diversity and bacterial composition in patients with hemodialysis, also revealed high-variability profiles of gut microbiome among patients with hemodialysis. Moreover, a randomized controlled trial indicated that treatment with β-glucan prebiotics significantly changed intestinal-derived uremic toxin levels and favorably affected gut microbiome [86].…”
Section: Intervention Strategies Through Regulating Gut Microbiota In...mentioning
confidence: 99%
“…Even though other sources of inflammation beyond CKD/uremic toxins (more than 25% of which are dietary o gut-derived) [ 24 , 25 , 26 ], such as infections or thrombotic events related to vascular access in HD patients, peritonitis in patients undergoing peritoneal dialysis, infections and immunosuppression in transplant patients, the intrinsic mechanisms associated with the development of a proinflammatory milieu is comparable in all CKD patients [ 2 ]. Further inflammatory factors are summarized in Figure 1 .…”
Section: Mechanisms Of Inflammation In Ckd and Their Relation To Maln...mentioning
confidence: 99%